Application of Problem-Based Learning Model to Improve Student Learning Outcomes in Biology Subjects - Dewi, Imega Syahlita; Ningtyas, Fitria Wahyu (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
This study was conducted with the aim of improving student learning outcomes in biology subjects by using the Problem Based Learning (PBL) learning model in class X-6 SMA Negeri 2 Nganjuk. This type of research is a class action research (PTK). The subjects were students of class X-6 SMA Negeri 2 Nganjuk totaling 30 students. The PTK design includes planning, action and observation, and reflection. Data collection techniques used observation, tests, and documentation. Data analysis using comparative quantitative methods. The results showed an increase in the percentage of learning outcomes, namely in cycle I by 40%, while in cycle II by 60%. This was accompanied by an increase in the average student learning outcomes in cycle I of 73.01, while in cycle II it was 82.1. Thus it can be concluded that the use of the Problem Based Learning (PBL) learning model in learning biology can improve student learning outcomes.